Implementation of Lean Six Sigma framework in a large scale industry: a case study. (19th March 2019) - Trehan, Rajeev; Gupta, Ajay; Handa, Mohit
In the present competitive scenario most of the companies are using improvement strategies like lean and Six Sigma for obtaining good quality products, reduction in overall cost and for enhancing availability of equipment. Lean and Six Sigma are two different tools which are used in combination for operational excellence. It provides a framework for waste reduction and elimination of non-value added activities along with variability reduction tools. Lean tools reduce the waste and non-value adding activity and enhance the effectiveness of equipment, tools and machines. Six Sigma tools helps in decision making based on data which finally reduce the variability in the process. In this case study, Lean Six Sigma framework is implemented to reduce the defects which occurred during the manufacturing process in a bulb manufacturing company in India. The framework used combines the lean as well as Six Sigma tools to mitigate the defects and increase the customer satisfaction.